PEKERJAAN PERBAIKAN JALAN LEUWEUNGHAPIT KEDUNGKENCANA PERKERASAN FLEXIBEL PAVEMENT DAN RIGID PAVEMENT - Hadi, Anjas (Universitas Majalengka, 2021)
ABSTRACT In general, roads are built as infrastructure to facilitate mobility and accessibility of socio-economic activities in the community. The existence of highways is increasing to support economic growth, agriculture and other sectors. Consider the very important benefits of sector development and road maintenance in the interests and development of planning, implementation and maintenance. Leuweunghapit - Kedungkencana road that connects several villages in Ligung District and the border of Cirebon Regency, Kedungkencana, Kedungsari and Ampel villages. Ligung District is repairing damage to some of these roads. This study discusses to determine the type and level of damage on the road surface and determine the value of damage to road damage, as well as providing evaluation of repairs. In the planning of road pavement the methods used are the 1987 Bina Marga Method and the 1986 ASSHTO (Association of Road Traffic Officials of the United States) with plans for the next 20 years, materials and road life plans. From the two methods ASSHTO and Bina Marga can be broken down higher than the surface of each layer, for compacting the upper foundation layer (base layer) and lower foundation layer (base layer). weak and suboptimal compaction in the foundation layer. Keywords: Pavement Flexibel Pavement, Rigid Pavement Pavement and Pavement Pavement